THE VALUES OF FREE FATTY ACIDS IN THE BLOOD IN WOMEN WITH METABOLIC SYNDROME IN THE POSTMENOPAUSAL PERIOD - Nurxan Muxamedova (Central Asian Journal of Medicine, 2023)
Metabolic syndrome (MS), which includes a number of systemic clinical and biochemical processes (insulin resistance, abdominal obesity, dyslipidemia, arterial hypertension), attracts close attention of general practitioners. The risk factors and pathological processes leading to the development of this syndrome remain controversial. Several hypotheses for the development of MS have been proposed, of which the theory of insulin resistance is the leading one. To date, all possible causes and mechanisms for the development of MS have not been finally disclosed. Non-esterified fatty acids play an important role in the development of MS.